Shear behavior of full-scale prestressed concrete double tee beams with steel-wire meshes. (1st April 2023) - Xiong, Xueyu; Zhang, Yang; Ge, Yipeng; Shi, Hairong; Musa, Moneef Mohamed Elobaid; Yao, Gangfeng
Abstract: Prestressed concrete double tee (PCDT) members have been widely used in parking buildings with large spans and heavy loads. To investigate the shear behavior of PCDT members, four full-scale PCDT members with steel-wire meshes were tested under monotonic loading in this paper. The two beam-end zones of each specimen were loaded to failure. The parameters studied in-depth were the ratio of the shear span to the effective depth λ and the area of prestressing steel strands. The failure modes, the strain of concrete and steel bars, shear force-deflection curves, cracking load, and shear strength were discussed in detail. The test results show that the variation of the ratio of the shear span to the effective depth λ and the area of prestressing steel strands have a significant effect on the inclined crack distribution of the PCDT members. The deformation capacity of PCDT members increases with an increase in the ratio of shear span to effective depth λ and the area of prestressing steel strands. The shear strength decreases with an increase in the ratio of shear span to effective depth λ and increases with an increase in the area of prestressing steel strands. PCDT members have good crack closure performance and deformation recovery ability after removing the load. Furthermore, an analytical model was proposed to predict the shear strength of PCDT members, which considers the effect of the ratio of shear span to effective depth λ, steel-wire meshes, prestressing steel strands, and the flanges of beams. For an analytical model, the key parameters of the shear-compression zone were established based on the cross-section strain analysis and Rankine's failure criterion. The calculation results show that the proposed model can accurately predict the shear strength of PCDT members. The average predicted-to-test shear strength ratio and the integral absolute error are 0.989 and 0.071, respectively. Highlights: Four full-scale PCDT members with steel-wire meshes were tested to investigate the shear performance. The variation of λ and the area of prestressing steel strands have a significant effect on the inclined crack distribution. The prestressing steel strands can restore the deformation of the PCDT members after shear failure. An analytical model considers the effect of steel-wire meshes, prestressing steel strands, and the flanges of beams. The proposed model can accurately predict the shear strength of PCDT members.